Adherence to WHO guidelines on severe pneumonia management in children and its impact on outcome: an observational study at Jinka General Hospital in Ethiopia - La Vecchia, Adriano; Teklie, Bereket Gebremedhin; Mulu, Dagmawi Awoke; Toitole, Kusse Koirita; Montalbetti, Francesca; Agostoni, Carlo; Hessebo, Tesfayesus Tefera; Tsegaye, Ademe; Pietravalle, Andrea; Manenti, Fabio; Tognon, Francesca; Pisani, Luigi; et al. (Frontiers in Public Health, 2023)
Introduction: Poor adherence to guidelines during empirical antibiotic prescription in low-income countries could increase antimicrobial resistance without improving outcomes. Revised World Health Organization (WHO) guidelines published in 2014 on childhood (2-59 months) pneumonia re-defined the classification of severe pneumonia and changed the first-line treatment. The adherence to WHO guidelines in southern Ethiopia at the hospital level is unknown. We sought to determine the adherence to WHO guidelines on severe pneumonia first-line treatment in children in an Ethiopian referral hospital and assess the impact of non-adherence on patient outcomes. Methods: observational study of all children (2-59 months) clinically diagnosed with severe pneumonia admitted to the Pediatric Ward of Jinka Hospital in one year from 1st June 2021 to 31st May 2022. Exclusion criteria were a known HIV infection, an ongoing antibiotic treatment before the event not correlated to acute pneumonia, or other severe bacterial infection confirmed or suspected. Adherence to guidelines was defined as a first-line treatment with ampicillin or benzyl penicillin and gentamicin at the recommended dose. We compared the patients treated adherently vs non-adherently. The chi-square or Fisher’s exact tests were used for categorical variables and the Mann-Whitney U-test for continuous ones. Multivariate logistic regression was used to evaluate the association between adherence and demographic and clinical characteristics. Results: During the observational period, 266 patients were registered as having severe pneumonia with an age between 2-59 months. After excluding 114 patients due to missing charts or other exclusion criteria, a total of 152 patients were included in analysis. Of these, 78 (51%) were female and with a median age of 10 months (IQR 7-14). Overall, 75 (49%) patients received therapy according to WHO guidelines. Compared to patients treated adherently to the guidelines, patients treated not adherently had similar outcomes (median length of stay 3 (IQR 3-5) and 4 (IQR 3-6) days respectively, median duration of oxygen therapy 2 (IQR 1-3) for both the groups and a self-discharge rate of 5% and 6.5% respectively). Conclusions: The adherence to the revised WHO guideline was limited and not associated with outcomes. Efforts should focus on reducing the gap between theory and practice.